ANALISIS PENGARUH CKPN, LDR, LIQUIDITY GAP DAN BOPO TERHADAP PROFITABILITAS PERBANKAN DI INDONESIA (STUDI KASUS PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016) - Tira Sutriani; Riche Fermayani (STIE Perbankan Indonesia, 2018)
This study aims to determine how the analysis of the influence of ckpn, ldr, liquidity gab and bopo on banking profitability. Secondary data collection is obtained from internet media by downloading annual report of banking company which listed on BEI from 2012 until 2016 through website www.idx.co.id. The method of analysis used is multiple linear regression, t test, f test, and test of coefficient of determination (R2). The results of this study indicate that variable ckpn, ldr and liquidity gab have a positive and significant influence on bank profitability, while bopo has a significant negative effect on banking profitability. Test f shows the independent variables ckpn, ldr, liquidity gab and bopo silmultan has an influence on the dependent variable profitability banking. From the result of determinant coefficient test, the result of ability of independent variable that is ckpn, ldr, liquidity gab and bopo explain dependent variable that is bank profitability equal to 77,4% while the rest explained by other factor not explained in this research.